Diseño y prototipo de dispositivo de lentes con corrección óptica incorporadas en los cascos para motocicletas. - Barragan Huertas, Hector David (Universidad Antonio Nariño, 2021)
The use of motorcycles has become a practical and affordable means of transport, being one of the most used in Latin America (1), however, protection measures must be taken into account as well as instructions and requirements on a suitable handling of the motorcycle, therefore, the helmet is essential for the protection of drivers